2012
DOI: 10.1128/jcm.00278-12
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Airway Microbiota in HIV-Infected Pneumonia Patients

Abstract: cDespite the increased frequency of recurrent pneumonia in HIV-infected patients and recent studies linking the airway bacterial community (microbiota) to acute and chronic respiratory infection, little is known of the oral and airway microbiota that exist in these individuals and their propensity to harbor pathogens despite antimicrobial treatment for acute pneumonia. This pilot study compared paired samples of the oral and airway microbiota from 15 hospitalized HIV-infected patients receiving antimicrobial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 38 publications
5
75
0
1
Order By: Relevance
“…Alterations in the oral microbiome have important implications for disease processes (29), such as periodontal diseases (30), but may precede changes in the lung. Previous work by one of the LHMP collaborators identified increased abundances for a large number of taxa in oral samples from HIV-infected patients with pneumonia, in comparison to HIV-uninfected control subjects (31). A culture-based study identified abundant Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the oral microbiome have important implications for disease processes (29), such as periodontal diseases (30), but may precede changes in the lung. Previous work by one of the LHMP collaborators identified increased abundances for a large number of taxa in oral samples from HIV-infected patients with pneumonia, in comparison to HIV-uninfected control subjects (31). A culture-based study identified abundant Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the microbial composition of the lung in healthy individuals is necessary to understand changes that may occur with respiratory diseases such as chronic obstructive pulmonary disease (COPD) or in immunosuppressed individuals such as those with HIV infection. Culture-independent techniques investigating various respiratory samples have produced conflicting conclusions about the composition of the lower respiratory tract microbiome (6)(7)(8)(9)(10). Controversy persists over the existence of distinct organisms in the lung and whether bacteria in the lungs represent microaspiration of oral microbiota or whether upper respiratory contamination of lower respiratory tract samples is caused by passing a bronchoscope through the oral cavity to obtain lung samples.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…Before bronchoscopy, 10 to 50 ml of sterile 0.9% saline were washed through the bronchoscope and collected as a control for DNA in the bronchoscope. Bronchoalveolar lavage (BAL) was performed according to standardized procedures developed to minimize oral contamination (10). Participants gargled with an antiseptic mouthwash (Listerine) immediately before topical anesthesia.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Iwai and colleagues compared the oral and airway microbiome in HIV-infected patients treated with antimicrobials for acute pneumonia (89). The lungs exhibited a significantly higher relative abundance of multiple members of the Proteobacteria, including several known pathogens such as Klebsiella pneumoniae and Pseudomonas species, which may contribute to the high prevalence of recurrent pneumonia in HIVinfected patients.…”
Section: Lessons Learned From the Study Of Airway Microbiota In Lung mentioning
confidence: 99%